Vitrectomy for Proliferative Diabetic Retinopathy in a Patient with Heparin-Induced Thrombocytopenia - Fujii, Tomoko (Case Rep Ophthalmol, 2016)
INTRODUCTION: In this study, we report a case of proliferative diabetic retinopathy in a patient with heparin-induced thrombocytopenia (HIT) in whom vitrectomy was performed with good results. CASE: A 57-year-old man presented with a chief complaint of decreased visual acuity (VA) in the left eye. Corrected VA of the left eye was 0.03, and ophthalmic examination showed fibrovascular membranes along the vascular arcade and a combined rhegmatogenous-traction retinal detachment with a macular hole. The patient began hemodialysis for diabetic nephropathy in March 2014; thrombocytopenia developed after dialysis was started, and HIT was diagnosed after further evaluation. Argatroban hydrate was being used during dialysis. Treatment was switched from warfarin to argatroban hydrate 6 days prior to vitrectomy being performed on the patient's left eye. Although there was bleeding with somewhat difficult hemostasis during the intraoperative treatment of the fibrovascular membranes, surgery was completed without complications and the postoperative course was good. DISCUSSION: Vitrectomy was performed with good results in this patient with HIT. Treatment with argatroban hydrate during surgery enabled surgery without the danger of intraoperative clotting.